Effect of f–d and d–d Interactions on Dielectric and Optical Properties of Pyrochlore Eu2−xFexTi2O7 - Alam M.; Pal A.; Ghosh S.; Singh R.K.; Ghosh A.K.; Chatterjee S. (My University, 2025)
X-ray diffraction, Raman spectroscopy, Fourier-transform infrared (FTIR) spectroscopy, dielectric property, and UV–vis spectroscopy studies of pyrochlore Eu2−xFexTi2O7 have been performed. The X-ray pattern shows that Eu2−xFexTi2O7 has a pure pyrochlore phase up to x = 0.2. The structural analysis shows a strong distortion of TiO6 octahedral due to the presence of the interstitial anionic vacant site. A significantly increased band intensity of FTIR spectrum with Fe doping suggests the enhanced anionic disorder in the system. The broadening of Raman peaks with increasing x supports the increased disorder in TiO6 octahedral. Dielectric study of Eu2Ti2O7 shows a diffused dielectric transition below 150 K. The dielectric diffusiveness and transition temperature get enhanced with Fe doping due to enhanced anionic distortion. The dielectric constant of Eu2−xFexTi2O7 is also increased on Fe doping. The UV–vis spectrum exhibits a strong absorbance in the UV region and a redshift with Fe doping. The Tauc plot of UV–vis spectrum shows multiple successive valence band edges and the bandgap gets reduced with Fe doping due to the formation of new interbands. Thus, these materials are interesting for people searching for material to be used in tunable electrical and optical devices. © 2022 Wiley-VCH GmbH.